PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN INSYA’ UNTUK MENINGKATKAN MAHARAH KITABAH BAHASA ARAB - Ahmad Husein; Anwar Sidik (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study aims to analyze the utilization of Artificial Intelligence (AI) in insya’ (Arabic writing composition) learning and its effect on improving students’ maharah kitabah (Arabic writing skills). The background of this research lies in the persistent challenges faced by students in developing Arabic writing competence, including limited vocabulary mastery, weak understanding of Arabic sentence structures, and the dominance of conventional teacher-centered approaches. This study employs a qualitative method with a library research (kajian pustaka) approach, analyzing relevant scientific literature, journal articles, and prior studies related to AI integration in Arabic language learning. The findings reveal three key dimensions: first, AI tools such as ChatGPT, Al-Qalam AI, and Natural Language Processing (NLP)-based applications have been effectively implemented in insya’ learning through features including automatic grammar correction, real-time feedback, contextual vocabulary suggestions, and translation assistance; second, the use of AI significantly improves students’ writing skills by enhancing motivation, engagement, and accuracy in applying Arabic linguistic rules; third, while AI offers transformative opportunities for adaptive and personalized learning, it also presents challenges such as the risk of over-reliance on technology and the potential decline in critical thinking if usage is not properly managed. This study concludes that AI serves not merely as a technical aid, but as a catalyst for more effective and innovative Arabic writing instruction in the digital era.